2017
DOI: 10.1038/nature24661
|View full text |Cite
|
Sign up to set email alerts
|

A gut bacterial pathway metabolizes aromatic amino acids into nine circulating metabolites

Abstract: The human gut microbiota produces dozens of metabolites that accumulate in the bloodstream1,2, where they can have systemic effects on the host. Although these small molecules commonly reach concentrations similar to those achieved by pharmaceutical agents, remarkably little is known about the microbial metabolic pathways that produce them. Here we use a combination of genetics and metabolic profiling to characterize a pathway from the gut symbiont Clostridium sporogenes that generates aromatic amino acid meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

25
799
3
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 892 publications
(891 citation statements)
references
References 26 publications
25
799
3
8
Order By: Relevance
“…Tryptophan is an essential amino acid important for the generation of a range of bioactive molecules, including serotonin and melatonin [51]. The host utilizes the majority of diet-derived tryptophan, but the gut microbiota also metabolize a portion resulting in indolecontaining molecules [52,53]. Several of these are aryl hydrocarbon receptor ligands and regulate mucosal immunity, which will be discussed in later sections, and is also discussed in detail in a review by Roager and Licht [54].…”
Section: Review Series: Translating Immunometabolismmentioning
confidence: 99%
See 2 more Smart Citations
“…Tryptophan is an essential amino acid important for the generation of a range of bioactive molecules, including serotonin and melatonin [51]. The host utilizes the majority of diet-derived tryptophan, but the gut microbiota also metabolize a portion resulting in indolecontaining molecules [52,53]. Several of these are aryl hydrocarbon receptor ligands and regulate mucosal immunity, which will be discussed in later sections, and is also discussed in detail in a review by Roager and Licht [54].…”
Section: Review Series: Translating Immunometabolismmentioning
confidence: 99%
“…Analysis of the metabolic pathway involved revealed that there are 12 resulting metabolites, nine of which accumulate in host serum, including indolepropionic acid (IPA) [52]. Analysis of the metabolic pathway involved revealed that there are 12 resulting metabolites, nine of which accumulate in host serum, including indolepropionic acid (IPA) [52].…”
Section: Review Series: Translating Immunometabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…Amino acids play an important role in regulating the nutritional metabolism of the host. It can be inferred that lysine catabolism in the intestinal tract may be related to intestinal micro-organisms Dodd et al (2017). Proteins are absorbed in the form of amino acids in the animals' body(Dai, Zhang, Wu, & Zhu, 2010).…”
mentioning
confidence: 99%
“…These gut bacteria has coevolved with the human body to perform numerous beneficial functions ranging from being simple fermenters of food to having profound effects on the host immune development, metabolism and food preferences, brain development, stress responses, pain and behavior [1][2][3][4][5]. Consequently, disruptions or alterations in this resilient relationship is a significant factor in many diseases such as inflammatory gastrointestinal diseases, and neuropsychiatric disorders, including depression [1,[6][7][8].…”
Section: Introductionmentioning
confidence: 99%